Beyond Confinement: A Legal Exploration of the Rights of Vulnerable Groups in the Indonesian Correctional System - Sianturi, Tony Budianto; Fadlan; Ramon Nofrial; Erniyanti; Soerya Respationo (Enigma Institute, 2024)
The Indonesian correctional system, while tasked with upholding justice, grapples with the challenge of safeguarding the rights of vulnerable groups within its confines. This study delves into the legal framework and practical realities concerning the rights of these groups, encompassing women, children, the elderly, and individuals with disabilities, within the Indonesian prison system. The research employs a hybrid methodology, integrating normative legal analysis with empirical insights gleaned from interviews and case studies. The normative legal analysis scrutinizes pertinent laws, regulations, and international human rights instruments to gauge the extent of legal protection afforded to vulnerable groups in the correctional context. The empirical component, through interviews with correctional officers, inmates, and legal experts, sheds light on the lived experiences of these groups and the practical implementation of their rights. The study reveals a complex interplay between legal provisions and ground realities. While Indonesian law enshrines the rights of vulnerable groups, their actualization within the correctional system faces formidable obstacles. Overcrowding, inadequate healthcare, and limited access to rehabilitation programs disproportionately impact these groups, hindering their reintegration into society. In conclusion, our study underscores the imperative of bridging the chasm between legal safeguards and their practical implementation. It advocates for targeted interventions, including enhanced healthcare provisions, specialized rehabilitation programs, and heightened sensitivity training for correctional staff, to ensure the holistic well-being and successful reintegration of vulnerable groups within the Indonesian correctional system.